AETIOLOGY AND TYPES OF NEONATAL SEIZURES PRESENTING AT AYUB TEACHING HOSPITAL ABBOTTABAD - Najeeb, Shahzad; Qureshi, Azhar Munir; Rehman, Anis -ur-; Ahmad, Fayaz; Shah, Sher; Khan, Asfand Yar; Siddiqui, Tahir Saeed (Journal of Ayub Medical College Abbottabad, 2012)
Background: Neonatal seizures (NS) affect approximately 1% of neonates. Clonic, tonic, myoclonic and subtle seizures are the common types. Birth asphyxia, sepsis, metabolic derangements, intracranial bleed, kernicterus, tetanus and 5th day fits are the common aetiologies. This study was planned to evaluate the types and causes of neonatal seizures. Methods: It was a descriptive case series conducted at Ayub Teaching Hospital, Abbottabad from 12th December 2006 to 25th September 2007 on neonates having seizures. Serum chemistry, blood counts, cerebrospinal fluid examination and cranial ultrasound were done in all patients. Blood culture, renal and liver function tests, computerised tomography scan, metabolic and septic screening was done in selected patients. Descriptive statistics were applied for analysis. Results: Tonic clonic seizure was the commonest type (28%) followed by multi-focal clonic, and focal tonic seizures (25% each). Birth asphyxia was found to be the main aetiology (46%). Conclusion: Tonic clonic seizure was the commonest type and birth asphyxia the main aetiology identified in the majority of neonatal seizures. Keywords: Neonatal seizures, Aetiology, Seizures, Epilepsy, Neonates